2012
DOI: 10.1016/j.juro.2011.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Moderate and High Grade Vesicoureteral Reflux After a First Febrile Urinary Tract Infection in Children: Construction and Internal Validation of a Clinical Decision Rule

Abstract: A clinical decision rule was derived to enable a selective approach to cystography in children with urinary tract infection. The rule predicts high grade vesicoureteral reflux with approximately 85% sensitivity and avoids half of the cystograms that do not find reflux grade III or higher. Further validation is needed before its widespread use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
3
13
0
2
Order By: Relevance
“…Similar to our results Leroy and colleagues [25][26][27][28] have also shown that most patients with low-grade VUR had low procalcitonin concentration and did not need VCUG or RNC in the fi rst episode of febrile UTI. This association was assumed to be due to the increased risk of renal scarring with high-grade VUR is increased.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Similar to our results Leroy and colleagues [25][26][27][28] have also shown that most patients with low-grade VUR had low procalcitonin concentration and did not need VCUG or RNC in the fi rst episode of febrile UTI. This association was assumed to be due to the increased risk of renal scarring with high-grade VUR is increased.…”
Section: Discussionsupporting
confidence: 91%
“…The association of PCT values with VUR in children with febrile UTI remains controversial [25][26][27][28] The current study shows a signifi cant difference in PCT values between children with and without VUR, in accordance to the previously published data [25][26][27][28][31][32][33][34] . An earlier multicenter study of 398 patients in 8 centers in 7 European countries, in which DMSA was not performed in all patients [26] and strongly showed that PCT is a predictor of VUR independently of its relationship with early parenchymal involvement regardless of the urine-collection technique used for the diagnosis of UTI.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations